FACTORS AFFECTING THE EFFICIENCY OF REFORMS IN THE MANAGEMENT SYSTEM OF HIGHER EDUCATION INSTITUTIONS - Soliyev, Ibodulloxon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Socio-economic development in the 20th century and the present period is explained by the sharp increase of the human factor in the composition of resources. On the one hand, this resource has risen to a new level in terms of quality, and on the other hand, society's investments are increasingly directed to its creation. In the article, the opinions about the role of higher education in the formation of human capital are scientifically based.